The Effect of Students’ Personal Photograph as Media in Teaching Writing Ability in SMPN 1 Wawotobi - Hasriati, Hasriati; Rama, Asri Nofa (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2021)
The purpose of study is to examine whether significant differences exist in students’ pretest and posttest writing ability as a result of experiencing student’s personal photograph as media and to examine whether significant differences in students’ test scores exist between those attending personal photograph as media and those experiencing conventional instruction without media at the eighth students grade in SMPN 1 Wawotobi. The population of this research was the entire the eighth grade students of SMPN 1 Wawotobi who enrolled in academic year 2016/2017. The data were obtained from students’ pre-test and posttest scores. The pre-test was given before the treatment applied and the posttest is given after the treatment finished. The finding revealed that significant differences exist in students’ pretest and posttest writing ability as a result of experiencing instruction using personal photograph as media, p (.000) less than 0.05. The finding also indicated that significant differences in students’ test scores exist between those attending personal photograph as media and those experiencing conventional instruction p (.000) less than 0.05. In light of all these findings, students’ personal photograph significantly affected students’ writing ability. Keywords: Personal Photograph, Writing Ability, Effect